Characterization of Bacterial Nanocellulose - Graphite Nanoplatelets Composite Films - Susilo, Bili Darnanto; Suryanto, Heru; Aminnudin, Aminnudin (Universitas Negeri Malang, 2021)
Bacterial cellulose (BC) was synthesized from pineapple peel extract media with addition of fermentation agent bacteria Acetobacter xylinum. BC was disintegrated from the pellicle into bacterial nanocellulose (BNC) by using a high-pressure homogenizer (hph) machine, which has a three-dimensional woven nanofibrous network. The synthesis of composite films started when BNC, graphite nanoplatelets, and cetyltrimethylammonium bromide (CTAB) were homogenized using an ultrasonic homogenizer then baked on a glass mold at a temperature of 80 degrees Celcius for 14h. A scanning electron microscope (SEM) was used to analyze its morphology. X-Ray diffraction spectra were used to analyze the composite films structure. The functional groups of the composite films were analyzed using the FTIR spectrum. SEM micrograph shows that GNP was evenly distributed into BNC matrix after CTAB addition. GNPs are shown as flat and smooth flakes with sharp corners. Some peak corresponds O-H, C-H, C≡C, and CH3 stretching was identified by using FTIR spectroscopy at wavenumber 3379, 2893, 2135, and 1340 cm-1, respectively. XRD analysis shows that Crystalline Index (C.I) of BNC increases after 2.5 wt% addition of GNP. The presence of CTAB decreases C.I value of composite films. BNC/GNP composite films have the best mechanical properties with Young’s modulus about 77.01 ± 8.564.